Analysis of Human Development Index, Government Expenditure, Exports and Imports on Economic Growth in ASEAN-5 - Rohima, Siti; Junaidi, Junaidi; Nasyaya, Annada; Hamira, Hamira (Jurnal Ekonomi Pembangunan, 2023)
This study aims to analyze the Human Development Index, Government Expenditure, Exports and Imports on Economic Growth in Singapore, Philippines, Malaysia, Thailand, and Indonesia. Using secondary data the period 2010-2021. The method used is the Quantitative method using Panel Data Regression. Results of panel data regression, export variable product has a positive and significant effect on economic growth. These results reveal that to increase economic growth, it is necessary to increase export performance. Increasing export performance can be done in various ways, one of which is by improving the export administration system, increasing research and product development, improving infrastructure facilities and infrastructure, exchange rate stability and expanding non-traditional markets